(untitled) (Anclajes, 2021)
The questions around literary writing and its possibilities for representing violence and historical trauma is a current discussion in both philosophical and literary studies. This article addresses these complexities and examines, through a reading of the novel El profundo Sur (1999) by Argentine writer Andrés Rivera, the possibilities of the literary text as a device that tries to represent or depict violence and trauma through a fictional narrative. The novel takes as its setting and historical reference the massacre of workers in Buenos Aires in 1919, also known as the “Semana Trágica”. Rivera, whose aesthetics is marked by the use of the ellipsis, elaborates a reflection on language, fiction, and the reconstruction of a historical event through literature.